DEVELOPING SOCIALIZATION OF PRIMARY SCHOOL STUDENTS WITH AUTISM SPECTRUM DISORDER THROUGH ABA THERAPY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article addresses the issues of developing the socialization and social integration process of students with autism spectrum disorder (ASD) through Applied Behavior Analysis (ABA therapy). The study provides a scientific and practical analysis of the core ABA therapy technologies and mechanisms, such as reinforcement, prompting, fading, shaping, and chaining, which play a crucial role in forming social-communicative skills in children on the autism spectrum. Furthermore, the practical effectiveness of the "Turn-Taking Shaping" and "Request Shaping" methodologies—developed by integrating the DTT (Discrete Trial Training) model, PECS cards, and "Visual Schedule" technology—in developing communication, waiting for turns, and independent requesting skills among students is proven through experimental results.